The effects of asteroid layering on ejecta mass-velocity distribution and implications for impact momentum transfer - Raducan,SD; Davison,TM; Collins,GS (Planetary and Space Science, 2020)
Most bodies in the Solar System do not have a homogeneous structure. Understanding the outcome of an impact into regolith layers of different properties is especially important for NASA’s Double Asteroid Redirection Test (DART) and ESA’s Hera missions. Here we used the iSALE shock physics code to simulate the DART impact into three different target scenarios in the strength regime: a homogeneous porous half-space; layered targets with a porous weak layer overlying a stronger bedrock; and targets with exponentially decreasing porosity with depth. For each scenario we determined the sensitivity of crater morphology, ejecta mass-velocity distribution and momentum transferred from the impact for deflection, , to target properties and structure. We found that for a homogeneous porous half-space, cohesion and porosity play a significant role and the DART impact is expected to produce a between 1 and 3. In a two-layer target scenario, the presence of a less porous, stronger lower layer close to the surface can cause both amplification and reduction of ejected mass and momentum relative to the homogeneous upper-layer case. For the case of DART, the momentum enhancement can change by up to 90%. Impacts into targets with an exponentially decreasing porosity with depth only produced an enhancement in the ejected mass and momentum for sharp decreases in porosity that occur within 6m of the asteroid surface. Together with measurements of the DART crater by the Hera mission, these results can be used to test the predictive capabilities of numerical models of asteroid deflection.